Evaluating Perioperative Complications Surrounding Supracondylar Humerus Fractures: Expanding Indications for Outpatient Surgery. Issue 9 (5th October 2021) - Hockensmith, Lindsay H.; Muffly, Brian T.; Wattles, Mitchell R.; Snyder, Erin N.; McFarland, Braxton J.; Jacobs, Cale; Iwinski, Henry J.; Riley, Scott A.; Prusick, Vincent W.
Abstract : Background: Supracondylar humerus (SCH) fractures are one of the most common pediatric orthopaedic injuries. Described using the Wilkins modification of the Gartland Classification system, current practice guidelines give moderate evidence for closed reduction and percutaneous pinning of type 2 and 3 injuries, but little evidence exists regarding the appropriate surgical setting for fixation. The goal of this study was to evaluate the perioperative complication profile of type 3 fractures with maintained metaphyseal contact and determine their suitability for outpatient surgery. Methods: Skeletally immature patients with type 2 and 3 SCH fractures treated at a single, Level-1 trauma institution from March 2019 to January 2000 were retrospectively reviewed. A total of 1126 subjects were identified. Open, concomitant injuries, incomplete physical examination, initial neurovascular compromise, flexion-type fractures, ecchymosis, skin compromise, and those managed nonoperatively were excluded. Type 3 fractures were categorized as either "3M" versus type "3" ("M" denoting metaphyseal bony contact). Demographic data, neurovascular changes, and postoperative complications were collected. Categorical variables were evaluated using χ 2 or Fisher exact tests, and continuous variables analyzed using analysis of variance, with significance defined as a P -value <0.05. Results: A total of 485 patients (189 type 2, 164 type 3M, 132 type 3) met inclusion criteria. Sex and length of stay did not differ among groups. The incidence of neurovascular change between initial presentation and surgical fixation was significantly greater for type 3 fractures compared with other groups ( P =0.02). No child in the 3M group had preoperative neurovascular examination changes, compared with 3 patients with type 3 injuries. When directly compared with the 3M group, type 3 fractures had a higher incidence of neurovascular examination changes that trended towards significance ( P =0.08). There was no difference in postoperative complication rate between groups ( P =0.61). Conclusions: Our findings demonstrate that Gartland type 3 SCH fractures lacking metaphyseal bony contact, compared with types 3M and 2, are more likely to experience neurovascular examination changes between initial presentation and definitive surgical fixation. Type 3M fractures clinically behaved like type 2 injuries and, accordingly, could be considered for treatment on an outpatient basis. Level of Evidence: Level III—retrospective comparative study.